Molecular Epidemiology and Outcomes of Patients with Carbapenem-Resistant Enterobacteriaceae Bacteriuria, Atlanta 2012–2015. (October 2020) - Howard-Anderson, Jessica; Petit, Robert; Bower, Chris; Smith, Gillian; Ansari, Uzma; Halpin, Alison; Karlsson, Maria; Lawson, Adrian; Lutgring, Joseph; McAllister, Gillian; Farley, Monica; Jacob, Jesse; et al.
Abstract : Background: Carbapenem-resistant Enterobacteriaceae (CRE) represent a significant antibiotic resistance threat, in part because carbapenemase genes can spread on mobile genetic elements. Here, we describe the molecular epidemiology and outcomes of patients with CRE bacteriuria from the same city in a nonoutbreak setting. Methods : The Georgia Emerging Infections Program performs active, population-based CRE surveillance in Atlanta. We studied a cohort of patients with CRE (resistant to all tested third-generation cephalosporins and ≥1 carbapenem, excluding ertapenem) first identified in urine, and not in a prior or simultaneous sterile site, between 2012 and 2015. Whole-genome sequencing (WGS) was performed on a convenience sample. We obtained epidemiologic and outcome data through chart review and Georgia Vital Statistics records (90-day mortality). Using WGS, we created a core-genome alignment-based phylogenetic tree of the Klebsiella pneumoniae isolates and calculated the SNP difference between each sample. Using SAS version 9.4 software, we performed the Fisher exact test and univariable odds ratios (OR) with 95% CI to compare patient isolates with and without a carbapenemase gene. Results: Among 81 patients included, the median age was 68 (IQR, 57–74) years, and most were female (58%), black (60%), and resided in a long-term care facility 4 days prior to culture isolation (53%). Organisms isolated were K. pneumoniae (84%), Escherichia coli (7%), Enterobacter cloacae (7%), and Klebsiella oxytoca (1%). WGS identified at least 1 β-lactamase gene in 91% of the isolates; 85% contained a carbapenemase gene, the most frequent of which was bla KPC-3 (94%). Patients with CRE containing a carbapenemase gene were more likely to be black (OR, 3.7; 95% CI, 1.0–13.8) and to have K. pneumoniae (OR, 8.9; 95% CI, 2.2–35.0). Using a core-genome alignment of 3, 708 genes ( 63% of the complete genome), we identified a median of 67 (IQR, 23–3, 881) SNP differences between each K. pneumoniae isolate. A phylogenetic tree identified clustering around carbapenemase gene and multilocus sequence type (84% were ST 258) but not based on referring laboratory or county of residence (Fig. 1). Although 7% of patients developed an invasive CRE infection within 1 year and 21% died within 90 days, having a carbapenemase gene was not associated with these outcomes. Conclusions: Molecular sequencing of a convenience sample of CRE bacteriuria support K. pneumoniae ST258 harboring bla KPC-3 being distributed throughout the Atlanta area, across the healthcare continuum. Overall mortality was high in this population, but the presence of carbapenemase genes was not associated with worse outcomes. Funding: None Disclosures: None Disclosures: None Funding: None